The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jbm.a.36650
|View full text |Cite
|
Sign up to set email alerts
|

Aligned topography mediated cell elongation reverses pathological phenotype of in vitro cultured keloid fibroblasts

Abstract: Topography modified cell behavior remains less explored in diseased cells. This study investigated the reversing effect on the pathological phenotype of keloid fibroblasts via culturing cells on a parallel microgrooved surface. The results showed that this particular topography with 3 μm groove depth and 10 μm width could significantly elongate and align the cultured cells with reduced cell (nucleus) area and increased cell (nucleus) body aspect ratio and cell (nucleus) body major axis (p < 0.05). Importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…18 Therefore, it's important to introduce topographic cues into corneal tissue engineering for mimicking the microenvironment of cells. Previous studies have shown that the engineering substrate topography can signicantly inuence cell shape, 19,20 adhesion, [21][22][23] migration, 24 proliferation, [25][26][27] and differentiation. 28,29 For corneal cells, their behaviors are also regulated by surface topography.…”
Section: Introductionmentioning
confidence: 99%
“…18 Therefore, it's important to introduce topographic cues into corneal tissue engineering for mimicking the microenvironment of cells. Previous studies have shown that the engineering substrate topography can signicantly inuence cell shape, 19,20 adhesion, [21][22][23] migration, 24 proliferation, [25][26][27] and differentiation. 28,29 For corneal cells, their behaviors are also regulated by surface topography.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental protocol was approved by the Ethics Committee of Shanghai Ninth People’s Hospital. As previously reported [ 60 ], the keloid tissues of inflammatory outer zone were excised and the epidermis was removed. The remaining dermis was cut into small fragments and digested with 0.3% collagenase (SERA, Heidelberg, Germany) in Dulbecco’s modified Eagle’s medium (DMEM) (Hyclone, Logan City, UT) for 6 h at 37°C on a rotator.…”
Section: Methodsmentioning
confidence: 99%
“…The elongated cells gradually lost their fibrotic phenotype with reduced cell proliferation and cell cycle arrest in Sphase. These changes were accompanied with reduced expression of fibrotic markers, such as collagen, fibronectin, asmooth muscle actin and transforming growth factor-b1, along with attenuated SMAD and extracellular signal-regulated kinase phosphorylation levels (Huang, 2019).…”
Section: Pathomechanisms Of Keloidsmentioning
confidence: 98%
“…The cellular topography as a modifying factor of cell behavior was further investigated in a study were keloid fibroblasts were cultured on a surface with parallel microgrooves (Huang, 2019). In particular, growing cells in grooves with 3-mm depth and 10-mm width resulted in significant elongation and alignment of the cultured cells with reduced nuclear area.…”
Section: Pathomechanisms Of Keloidsmentioning
confidence: 99%